СПОРТИФИКАЦИЯ ТРАДИЦИОННЫХ КОННЫХ ИГР В КУЛЬТУРЕ КЫРГЫЗОВ - Илебаев Арстанбек Касенович (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: The article examines the process of sportification of traditional Kyrgyz equestrian games and competitions, which originated in ancient nomadic culture and have gradually transformed into regulated national sports. Based on historical sources, normative documents, and official sports classifications of the Kyrgyz Republic, the study analyzes the institutionalization of horse games such as at chabysh, zhamby atmay, zhorgo salysh, kok boru (ulak tartish), kyz kuumai, oodarysh, and tyyin enmei. Particular attention is paid to the standardization of competition rules, age and weight categories, distance regulations, safety requirements, and organizational frameworks introduced since the mid-twentieth century. The article demonstrates that the transformation of traditional equestrian practices into national sports contributed to the preservation of cultural heritage, the promotion of physical and moral education, and the strengthening of national identity. At the same time, sportification led to the limitation of archaic elements and the adaptation of these games to modern sporting norms. The study highlights the dual role of equestrian sports as both a cultural tradition and a contemporary form of organized physical activity.